Energy metabolism and maternal-fetal tolerance working in decidualization - Meng, Xinhang; Chen, Chunqin; Qian, Jinfeng; Cui, Liyuan; Wang, Songcun (Frontiers in Immunology, 2023)
One pivotal aspect of early pregnancy is decidualization. The decidualization process includes two components: the differentiation of endometrial stromal cells to decidual stromal cells (DSCs), as well as the recruitment and education of decidual immune cells (DICs). At the maternal-fetal interface, stromal cells undergo morphological and phenotypic changes and interact with trophoblasts and DICs to provide an appropriate decidual bed and tolerogenic immune environment to maintain the survival of the semi-allogeneic fetus without causing immunological rejection. Despite classic endocrine mechanism by 17 β-estradiol and progesterone, metabolic regulations do take part in this process according to recent studies. And based on our previous research in maternal-fetal crosstalk, in this review, we elaborate mechanisms of decidualization, with a special focus on DSC profiles from aspects of metabolism and maternal-fetal tolerance to provide some new insights into endometrial decidualization in early pregnancy.